IgA vasculitis, formerly known as Henoch-Schönlein purpura – the most common vasculitis in children - Jaszczura, Majka; Dyga, Katarzyna; Bryłka, Aleksandra; Góra, Anna; Machura, Edyta (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Henoch-Schonlein purpura (HSP) is the most common systemic vasculitis in children. It belongs to the group of small-vessel vasculitis associated with immune complexes, and the proper term is IgA vasculitis (IgAV). In HSP in the wall of small vessels, deposits of immune complexes composed of IgA1 and C3 complement component are found. The incidence of HSP is estimated at 3–26.7/100,000 children per year. The changes most often affect the skin, lower limbs, digestive tract, and kidneys and are accompanied by arthralgia and arthritis. In this review article we pay attention to the pathogenesis, possible clinical manifestations, irregularities in laboratory tests, and proper management of patients with HSP. The treatment should depend on the clinical condition of the patient and is primarily symptomatic. Good knowledge of the differentiation of clinical symptoms allows for quick diagnosis and the qualification of patients for appropriate supervision.